Health and Demographic Surveillance System (HDSS) in Matlab, Bangladesh - Nurul Alam; Taslim Ali; Abdur Razzaque; Mahfuzur Rahman; M. Zahirul Haq; Sajal Saha; Ali Ahmed; A.M. Sarder; M. Moinuddin Haider; Mohammad Yunus; Quamrun Nahar; Peter Kim Streatfield (2017)
Bangladesh, (icddr,b, former Pakistan SEATO Cholera Research Laboratory) set up a field diarrhoea hospital in Matlab in December 1963 for evaluating acceptability, safety and efficacy of cholera vaccines, including oral rehydration therapy, and studying the epidemiology, prevention and treatment of diarrhoeal diseases and other public health interventions.The evaluation studies required accurate count of population at risk for computing rates and ratios.Matlab HDSS (former DSS till 1999) was established in May 1966 for counting the de jure population and births, deaths and migrations with precise dates. 1 High rates of fertility and mortality and poor availability and accessibility of primary health care in rural areas provoked design and implementation of a quasi-experimental maternal and child health and family planning (MCH-FP) programme in one half of the surveillance area, keeping the other half as comparison receiving usual government health services, with the aim to estimate the programme effects on fertility and mortality reductions, using HDSS data. 2 Subsequently the MCH-FP programme, along with the HDSS, became a training site for programme planners and implementers from developing countries.